Characteristics of seminal plasma and cryopreservation of anoa (Bubalus sp.) semen obtained by electroejaculation - Yudi .; T.L. Yusuf; B Purwantara; D. Sajuthi; M Agil (Jurnal Ilmu Ternak dan Veteriner, 2011)
The population of anoa, which is an endemic fauna to Indonesia, was getting decrease caused by the illegal hunting and deforestation. Anoa is included in endangered species by IUCN, and Appendix I by CITES. The experiment aimed to characterize the seminal plasma contents and to cryopreserve the anoa semen for artificial insemination application in captivity. The experiment was carried out in Taman Safari Indonesia (Bogor). Semen was collected from 2 anesthetized males (4-10 years) by electroejaculation. Seminal plasma gained by centrifugation of ejaculate (3000 rpm, 20 minutes), and then was evaluated the biochemical contents. Other ejaculates were evaluated macroscopically and microscopically, and then extended in Tris and Na-citrate media to a total concentration of 100 billion cells mL-1. Extended semen was stored at 4oC, and evaluated the motility and viability every 12 h. Frozen semen was made in Tris medium added with 5% of glycerol. The seminal plasma of anoa contained total lipid, Na, Ca and Mg higher than the buffalo, but its total protein, K and Cl were lower. Electrophoresis of seminal plasma using by SDS-PAGE method showed 10 bands of proteins (17-148 kDa). The motility and viability of chilled-extended semen in Tris and Na-citrate media were not significantly different (P > 0.05) during 72 h of evaluation. Extended semen in both of media may applicable for AI program for 24-48 h. Post thawing motility of frozen semen was still low, 26.00 ± 9.62%. Therefore, it is necessary to improve each stages of semen processing, so the motility will increased and resulted high pregnancy in AI program. Key Words: Anoa, Seminal Plasma, Extended Semen, Frozen Semen, Electroejaclator